OUTCOMES OF THE PERFORMANCE-BASED FUNDING OF THE UNIVERSITIES OF APPLIED SCIENCES IN FINLAND - Koivisto, Matti (PEOPLE: International Journal of Social Sciences, 2018)
The Ministry of Education and Culture administers 23 universities of applied sciences (UASs) in Finland. Since 1994, the ministry has developed performance-based funding and steering methods to achieve its aims to enhance quality and performance of the UASs. In this paper, the outcomes of the performance-based policies are discussed. The analysis are based on annually collected performance indicators for all Finnish UASs. The results of the study indicate that performance-based funding has considerably increased efficiency of the UASs. For example, students pass today more courses during an academic year and are more likely to graduate in four years than a decade ago. Although the results are encouraging, the current performance-based funding has also received some criticism. The current model concentrates heavily on quantity and efficiency metrics. This has raised some concerns over quality of education. The findings of the study suggest that increased efficiency has had neither negative nor positive effect on quality measured by student satisfaction and employment. However, further studies and more data over a longer period are still needed before final conclusions can be made.